Similar mycorrhizal fungal communities associated with epiphytic and lithophytic orchids of Coelogyne corymbosa - Jiao Qin; Wei Zhang; Shi-Bao Zhang; Ji-Hua Wang (Plant Diversity, 2020)
Mycorrhizal fungi are essential for the growth and development of both epiphytic (growing on trees) and lithophytic (growing on rocks) orchids. Previous studies indicate that in lowland tropical areas, orchid mycorrhizal fungal compositions are correlated with the life form (i.e., epiphytic, lithophytic, or terrestrial) of their host plants. We therefore tested if a similar correlation exists in an orchid distributed at higher elevations. Coelogyne corymbosa is an endangered ornamental orchid species that can be found as a lithophyte and epiphyte in subtropical to subalpine areas. Based on high-throughput sequencing of the fungal internal transcribed spacer 2 (ITS2)-rDNA region of mycorrhizae of C. corymbosa, we detected 73 putative mycorrhizal fungal Operational Taxonomic Units (OTUs). The OTUs of two dominant lineages (Cantharellales and Sebacinales) detected from C. corymbosa are phylogenetically different from those of other species within the genus Coelogyne, indicating that different orchid species prefer specific mycorrhizal fungi. We also found that the Non-metric multidimensional scaling (NMDS) plots of orchid mycorrhizal fungi were not clustered with life form, the variations among orchid mycorrhizal fungal communities of different life forms were not significant, and most of the OTUs detected from epiphytic individuals were shared by the lithophytic plants, suggesting that orchid mycorrhizal associations of C. corymbosa were not affected by life form. These findings provide novel insights into mycorrhizal associations with endangered ornamental orchids.